Pendidikan Nilai Bela Negara Sejak Dini Pada Lingkup Keluarga - Ferdy Sopran Wamala; Nurul Qomariah (Badan Pendidikan dan Pelatihan Kementerian Pertahanan, 2025)
In the age of information disruption, our national standards faced very significant challenges. The unregulated dissemination of information frequently undermines national identity and can damage unity; thus, fostering national defense perspectives should commence at an early stage. This research contends that the family, as the smallest social unit for individuals, plays an important and essential role in cultivating national security knowledge and values from an early age. This research utilizes an extensive literature review methodology with a qualitative approach to systematically examine diverse library resources, including scientific journals, books, and prior research findings, via Google Scholar, Scopus, and DOAJ, covering publications from 2011 to 2025. Through the selection procedure, 25 appropriate research articles were found and thematically examined to identify trends in the development of national defense views within families. The study results consistently indicate that daily home activities, including discipline, ensuring cleanliness, orderliness, and fostering mutual cooperation, substantially and successfully nurture the foundation of patriotism and national defense awareness in children. These constructive habits progressively cultivate a child's character into a responsible individual who values the environment and possesses a sense of national identity. Literacy studies enable youngsters to comprehend the notion of national security not merely as doctrine, but as a fundamental aspect of communal existence. In conclusion, fostering patriotism from an early age is most effective and lasting when initiated within the home context, complemented with appropriate reading enrichment aligned with the child's developmental stage. This research provides practical recommendations for development, including daily activity guidelines, inspirational narratives, and national literacy modules aimed at assisting parents in imparting the significance of national defense at home. Consequently, we can cultivate a young generation that is not only innovative but also inspired with a feeling of responsibility, patriotism, and readiness to contribute constructively to the advancement of the nation.